Encouraging Musical Creativity in Montenegrin Primary Education – A Case Study - Martinovic Bogojevic, Jelena (Central European Journal of Educational Research, 2021)
The need to change the paradigm of music education, which primarily relies on performing and listening to music, implies a more systematic introduction of activities that would enable the direct involvement of children in the exploration of sounds and the creation of their own music. By analysing the curricula and textbooks for music education in Montenegrin primary schools, as well as examining the attitudes of teachers about the realisation of musical creativity in teaching practice, it was found that these activities are not given enough attention. In order to introduce innovations in practice, an action research study was conducted, during 2017/2018 school year with 30 fifth grade pupils in one primary school, belonging to the Southern region of Montenegro. The obtained results, based on the qualitative findings, showed the connection between the categories that make up musical creativity in the classroom: acquiring musical knowledge, developing musical skills, encouraging problem solving, developing critical thinking, supporting collaborative creativity, motivation and integrative teaching. Hopefully, the conducted research will contribute to a wide range of understanding of musical creativity in the classroom context, as one of the leading topics of contemporary music pedagogy.